Penggunaan Pelayanan Sistem Transportasi Umum Bus Berbasis Web - Agus Dendi RACHMATSYAH; Benny Wijaya; R. Burham Isnanto; Elly Yanuarti; Ari Amir Alkodri; Riyan Nugraha (Sekolah Tinggi Manajemen Informatika dan Komputer PalComTech, 2022)
Public transportation is the most important part for people especially those who do not have a private vehicle, from the past until now the public transportation mode bus is still quite popular, such as in Belinyu District, Bangka Regency, Bangka Belitung Islands. Passengers when they want to use this mode of transportation usually wait at the terminal or on the side of the road that is usually used by the bus, payment is made on the way with the bus conductor, the destination is conveyed by the bus conductor along with payment, but problems occur sometimes the bus departure information is not clear because information cannot be accessed direct by passengers not to mention when there are passengers who come from outside the area who often miss the bus and on holidays there is usually a congestion of passengers who do not get a seat because the system is still manual and ineffective. Therefore, a bus service information system is needed by utilizing web-based information technology, so that the information obtained by passengers is clearer, more effective and accessible so that no one misses the bus or the accumulation of passengers who do not get a seat. Where information and transactions can be accessed via the website. In this study using the Rapid application development (RAD) method. With this web-based bus service information system can help customers and improve company services.